Mass communication in the modern Arab world ongoing agents of change following the Arab spring - Hamdy, Naila Nabil, 1958-; Auter, Philip, 1963- (Rowman & Littlefield, 2022)
"This book introduces, explains, and explores communication in the modern Arab world. Focusing on contemporary times and the lasting effects of the Arab Spring, the book reveals how the unceasing growth of media and communication technologies have acted as agents of change and provides evidence of mass communication's potential to transform societies and cultures"--